Ballantyne syndrome: case report - Miranda Flores, Alan Francis (2015)
Ballantyne syndrome or mirror syndrome is a rare entity with the classic triad of fetal hydrops, generalized maternal edema and placentomegaly. There is high perinatal morbidity and mortality. The case of a 26 year-old with 25 weeks of gestation hospitalized at Instituto Materno Perinatal emergency for leg edema and decreased fetal movements is reported. Fetal hydrops and placentomegaly were diagnosed by ultrasound. Preeclampsia and fetal death occurred during hospitalization. Following vaginal delivery there was rapid improvement of symptoms and the patient was discharged 48 hours postpartum.